Tokyo ghoul. 11 - Ishida, Sui (Viz signature., 2017)
Amid clashes between Ghouls and the Commission of Counter Ghoul investigators at Doctor Kano's underground facility, Kaneki finds himself locked in battle with Special Class Ghoul investigator Yukinori Shinohara. When the battle subsides, the CCG discovers shocking evidence that leads them closer to discovering the truth behind Kano's sinister plans. --Publisher